1976
DOI: 10.1021/ba-1976-0158.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Physical Sputtering: A Discussion of Experiment and Theory

Abstract: The theory of sputtering of amorphous and polycrystalline materials has been further developed. Experimental results for the energy, mass, and angular dependence of sputtering yields and recent experiments on the sputtering of chemi sorbed gas and sputtering by molecular ions illustrate sev eral effects that are important in determining sputtering yields and, in particular, the relationship of these effects to Sigmund theory. There are several mechanisms which might lead to discrepancies between theory and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In [55], the energy distributions of the platinum atoms sputtered by argon ions with energies 0.1, 0.5, and 1.0 keV were obtained using the MD simulation. It was found that these distributions are close to those given by the Thompson formula [41] based on the theory of binary collisions [56]. In [57], the multi-time scale approach was used to simulate the sputtering of gold targets by Au and Ar ions with energy 0.5 keV.…”
Section: Sputtering Of the Targetmentioning
confidence: 62%
“…In [55], the energy distributions of the platinum atoms sputtered by argon ions with energies 0.1, 0.5, and 1.0 keV were obtained using the MD simulation. It was found that these distributions are close to those given by the Thompson formula [41] based on the theory of binary collisions [56]. In [57], the multi-time scale approach was used to simulate the sputtering of gold targets by Au and Ar ions with energy 0.5 keV.…”
Section: Sputtering Of the Targetmentioning
confidence: 62%
“…68, 80, 99, 109, 112, 192, 200, 251/t 398, 498-500. efficiency, 202 forces, 62,65,68,78,85,86,99 hardness, 66 530 SUBJECT INDEX (continued) models, 1,71,103,191 rates, 42,192,[204][205][206]216 The proceedings contain forty of forty-three research papers, together with floor discussions, presented at the Symposium. Specific topics covered include: L) mechanisms of abrasive machining and surface finishing; 2) technology of machining md surface finishing; 3) characterization of machined surfaces; and 4) effects of machining on the properties of ceramics.…”
Section: Resultsmentioning
confidence: 99%
“…Ion beam machining uses a directed stream of ions to sputter material atom-by-atom from the surface of the workpiece [75][76][77][78][79] with minimum damage leaving a surface which is atomically clean [80,81]. Atoms are ejected from the surface by the transfer of momentum from the incident ions when the transferred energy exceeds the binding energy (-10 eV) and the momentum vector of the atom points away from the surface.…”
Section: Laser Typementioning
confidence: 99%
“…A very popular sputtered atom energy distribution function (EDF) F(E) was developed by Thompson [19], which reads:…”
Section: Sputtering Modelsmentioning
confidence: 99%